(untitled) (Journal of Mathematics Mechanics and Computer Science, 2019)
We prove the theorems of the existence and uniqueness of the boundary value and conjugate problems for Puasson equation concerning pressure of a layer and initial and boundary value problem for diffusion equation concerning concentration of a gas mixture in the two-dimensional multi zone region. Moreover, we prove the theorems of the existence and uniqueness of the conjugate problems for the problems of definition of the pressure of a layer and concentration of a gas mixture.